Math Bilbul “Alaihisalam” as a Learning Innovation During Covid 19: Math Bilbul “Alaihisalam” Sebagai Inovasi Pembelajaran Saat Pandemi Covid-19 - Robia Astuti; Nurmitasari, Nurmitasari; Sutriningsih, Naning (Universitas Muhammadiyah Sidoarjo, 2021)
This research is a research and development that aims to produce an interactive learning media product in the form of an educational game Math BilBul